Green reactants act as natural precursor for facile synthesis of nanoparticles using Withania Somnifera (International Journal of Pharmaceutical Sciences and Drug Research, 2020)
Nanotechnology includes physical and chemical approaches intended for their phytofabrication of metal nanoparticles. Most of the time, these methods are not as safe as these are associated with the utilization of extremely noxious and hazardous substances that produce biological problems. Due to their manifold applications, various biological methods are gaining admiration for the fabrication of silver nanoparticles (AgNPs). The utilization of vegetative parts in the biosynthesis of nanoparticles (NPs) emerges as a commercial and ecological approach. The spectroscopic profile confirms the occurrence of a functional peak at 360 nm. Fourier transform infrared spectroscopy (FTIR) studies indicate that phenol groups are responsible for phytofabrication of NPs. The results of microbicidal screening confirm that broad spectrum of inhibition was found to be observed in 400 μL of biosynthesized AgNP against E. coli (23 mm) and B. cereus (22.3 mm) Therefore, the progress of simple photosynthesis methods avoid deleterious and harmful properties has fascinated major attention in this field.